L’implantation du Projet transdisciplinaire en santé communautaire à l’Université de Saint-Boniface - Archambault, Hélène; de Rocquigny, Janelle; Ba, Halimatou; Giasson, Florette; Lapointe, Gisèle (Reflets, 2014)

Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 1968–1986 - Arsenault, Mathieu; Martel, Marcel (Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 2017)
Les gains en matière de soins de santé mentale en français arrivent au compte-goutte entre 1968 et 1986. L'État ontarien agit avec prudence dans ce dossier. Malgré les pressions des individus et de l'Association canadienne-française de l'Ontario, la mise en place de soins de santé mentale en français s'est butée à de nombreux obstacles tels que la pénurie de personnel parlant français, les difficultés à attirer ce personnel et à les inciter à demeurer notamment dans le Nord, les carences du système d'éducation à former des francophones, les hésitations du gouvernement ontarien, mais aussi l'hostilité au fait français.

Diverging socioeconomic inequality in life expectancy of Francophones and Anglophones in Montréal, Québec: Tobacco to blame? - Auger, Nathalie; Harper, Sam; Barry, Amadou D. (Journal of Public Health: From Theory to Practice, 2013)
Aim We evaluated the ages and causes of death contributing to life expectancy gaps between economically advantaged and disadvantaged Francophones and Anglophones of Montréal, a Canadian metropolitan centre. Subject and Methods We partitioned the life expectancy gap at birth between socioeconomically disadvantaged and advantaged Francophones and Anglophones of Montréal (Québec) into age and cause of death components for two periods (1989–1993, 2002–2006). Changes in the contributions of causes over time were evaluated. Results Life expectancy was lower for disadvantaged Francophones and Anglophones by 5 years in men and 1.6 years in women compared with advantaged individuals. Over time, the socioeconomic gap widened for Francophones (men 0.3 years, women 2.8 years), due to smaller reductions in mortality from tobacco-related causes (cardiovascular, cancer, respiratory) in disadvantaged than in advantaged Francophones, especially after age ≥65 years (except lung cancer mortality that increased, particularly in disadvantaged women). The socioeconomic gap narrowed, however, for Anglophones (men 1.0 year, women 0.6 years), due to greater reductions in cardiovascular mortality in disadvantaged than advantaged Anglophones. Conclusion Socioeconomic inequalities in life expectancy decreased for Anglophones but increased for Francophones in Montréal due to underlying trends in tobacco-related mortality. Despite strong tobacco control laws in Canada, socioeconomic inequality in tobacco-related mortality is widening for Francophones in Montréal.

Life expectancy gap between the Francophone majority and Anglophone minority of a Canadian population - Auger, Nathalie; Harper, Sam; Barry, Amadou D.; Trempe, Normand; Daniel, Mark (European Journal of Epidemiology, 2012)
Language is an important determinant of health, but analyses of linguistic inequalities in mortality are scant, especially for Canadian linguistic groups with European roots. We evaluated the life expectancy gap between the Francophone majority and Anglophone minority of Québec, Canada, both over time and across major provincial areas. Arriaga’s method was used to estimate the age and cause of death groups contributing to changes in the life expectancy gap at birth between 1989–1993 and 2002–2006, and to evaluate patterns across major provincial areas (metropolitan Montréal, other metropolitan centres, and small cities/rural areas). Life expectancy at birth was greater for Anglophones, but the gap decreased over time by 1.3 years (52% decline) in men and 0.9 years (47% decline) in women, due to relatively sharper reductions in Francophone mortality from several causes, except lung cancer which countered reductions in women. The life expectancy gap in 2002–2006 was widest in other metropolitan centres (men 5.1 years, women 3.2 years), narrowest in small cities/rural areas (men 0.8 years, women 0.7 years), and tobacco-related causes were the main contributors. Only young Anglophones <40 years in small cities/rural areas had mortality higher than Francophones, resulting in a narrower gap in these areas. Differentials in life expectancy favouring Anglophones decreased over time, but varied across areas of Québec. Tobacco-related causes accounted for the majority of the current life expectancy gap.

Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

État de la situation et étude de modèles de soins de santé primaires offerts aux francophones vivant en situation minoritaire au Canada - Axion (2016)

Comparison of dietary intake between Francophones and Anglophones in Canada: Data from CCHS2.2 - Batal, Malek; Makvandi, Ewa; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective To compare the dietary intake and food choices between Francophone Canadians in a state of linguistic minority (outside of Quebec) and the English-speaking majority. Methods We used the 2004 Canadian Community Health Survey (CCHS) cycle 2.2 (general health and 24-hour dietary recalls) to describe dietary intake of Francophone Canadians (excluding Quebec) and compare them to the English-speaking majority. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. The mean differences in daily nutrient and food intake were assessed by t and chi-square tests. Results Differences in total energy and daily food intakes by language groups were not observed in the sample; however, significant differences in weekly consumption were found in different age and sex categories: lower fruits and vegetables consumption, and vitamins and macronutrients intakes for older Francophone men and higher intakes of energy and saturated fat from “unhealthy” foods for Francophone men 19–30 years of age. Based on the Acceptable Macronutrients Distribution Range (AMDR), approximately 50% of the sample exceeded their acceptable energy intake from saturated fats, and 80% were below their required intake of linoleic fatty acid. Conclusion We confirmed that belonging to Francophone minorities in Canada affects food choices and nutritional well-being of this population. The most vulnerable groups identified by our study were Francophone men in the youngest (19-30) and older (50 and over) age categories. The extent to which the cultural setting influences the diet and, in turn, the health of the minority population needs further examination.

Perceived Health status of Francophones and Anglophones in an official bilingual Canadian province - Bélanger, Mathieu; Bouchard, Louise; Gaboury, Isabelle; Sonier, Brigitte; Gagnon-Arpin, Isabelle; Schofield, Aurel; Bourque, Paul-Emile (Canadian Journal of Public health, 2011)
Objective: It has been reported that being part of a minority group may be negatively associated with self-perceived health. The objective of this analysis was to determine whether there are differences in perceived health between the Francophone minority and Anglophone majority in New Brunswick, the only officially bilingual province in Canada. Methods: Data from the first four primary cycles of the Canadian Community Health Survey (2001 to 2007) were obtained for 17,729 New Brunswick residents. Odds of reporting good health among Francophones and Anglophones were compared using multivariate logistic regressions accounting for age, health-related behaviours, socio-demographic variables, and medical conditions. Results: In the final models, Francophone men and women were less likely than Anglophones to report their health as being good, although these differences were not statistically significant (Odds ratio, 95% confidence interval: 0.88, 0.61–1.26; 0.71, 0.49-1.04, in men and women, respectively). Conclusion: This study suggests that being part of the linguistic minority in New Brunswick is not associated with statistically significant differences in self-perceived health.

Les inégalités sociales de santé chez les communautés francophones en situation minoritaire (CFSM) au Canada [numéro thématique] - Benoit, Monique; Bouchard, Louise; Garceau, Marie-Luce (Reflets, 2012)

Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

Citoyens de deuxième classe ? Perceptions de la santé et du système de soins chez les francophones du nord-est de l’Ontario - Bernier, Christiane (Francophonies d'Amérique, 2009)
Cette enquête a pour objectif d’analyser les représentations que les francophones vivant en situation minoritaire ont de leur santé et de celle de leur communauté, de même que leurs perceptions des systèmes de soins auxquels ils ont accès, particulièrement lorsqu’ils vivent dans des régions rurales ou éloignées. De type qualitatif, l’enquête a été réalisée dans le nord-est de l’Ontario auprès de 32 francophones provenant de dix villes différentes. Les résultats montrent que le mépris de la langue minoritaire, le manque de services et de considération pour les francophones ainsi que le faible intérêt accordé par le gouvernement aux usagers des régions éloignées sont les pivots autour desquels se construisent l’insécurité et les désillusions par rapport au système de santé de la province.

Programme d’accès aux services de santé et aux services sociaux en langue anglaise de la Côte-Nord - Bilodeau, Nancy; Paradis, Pascal; Morin, Sandra (Agence de la santé et des services sociaux de la Côte-Nord, 2011)

Professionnels de la santé et minorités de langue officielle au Canada, 2001 et 2006 (n°91-550-X) - Blaser, Christine (Statistique Canada, 2009)

Special report on French language health services planning in Ontario, 2009 - Boileau, François (Office of the French Language Services Commissioner, 2009)

Inventaires des services de santé en français dans l’Ouest canadien : entre improvisation et gouvernance : 2000‐2010 - Boily, Frédéric; Gagné, Learry (Revue Gouvernance, 2013)
La difficulté pour les communautés francophones en situation minoritaire au Canada d’obtenir des services de santé dans leur langue est bien connue. Le problème est encore plus criant dans l’Ouest canadien, défavorisé par une faiblesse démographique et une grande dispersion de la population par rapport à l’Est (surtout l’Ontario et le Nouveau-Brunswick). Dans ce contexte, la mobilisation des francophones pour la défense de leurs intérêts est essentielle. Ce projet porte sur les relations entre les gouvernements provinciaux de l’Ouest, le gouvernement fédéral et les groupes francophones minoritaires en matière de politique de santé. Nous proposons de nous concentrer sur les provinces de la Colombie-Britannique, de l’Alberta et de la Saskatchewan pour la période récente allant de 2000 à 2010. L’analyse porte principalement sur les facteurs en politique publique qui ont permis à ces groupes de revendiquer un certain nombre de services de santé. Nous établissons une relation entre la participation active du fédéral durant cette période, la participation plutôt passive des provinces, et la préférence pour les projets de santé publique où le fédéral a pu jouer un rôle sans empiéter sur les pouvoirs provinciaux.

Littératie en matière de santé : des moyens novateurs de stimuler la prise en charge par la population francophone du Nord-Est du Nouveau-Brunswick - Boivin, Nathalie; Réseau Communauté en santé de Bathurst (Francophonies d'Amérique, 2009)
L’Organisation mondiale de la santé (OMS) définit la promotion de la santé comme le processus qui confère aux populations les moyens d’assurer une plus grande maîtrise de leur propre santé et de l’améliorer. Or, comment parler de prise en charge de sa santé alors qu’une partie importante de la population francophone du nord-est du Nouveau-Brunswick ne possède pas le niveau minimal d’alphabétisation requis pour fonctionner dans notre société actuelle ? Une démarche habilitante auprès de cette population a été menée. Les résultats préliminaires sont exposés, dévoilant les avantages et les obstacles d’une campagne médiatique.

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
a plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (Colloque 103 – L’offre des services de santé dans les langues minoritaires, 92e Congrès de l’Acfas, 2025)

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)

Santé mentale chez les francophones en situation linguistique minoritaire - Bouchard, Louise; Colman, Ian; Batista, Ricardo (Reflets, 2018)
Bien que la plupart des études considèrent l’importance des déterminants sociaux sur l’existence des troubles mentaux, aucune ne désagrège les données en fonction de l’appartenance à une communauté de langue officielle en situation minoritaire, un fait pourtant reconnu pouvant avoir un impact sur la santé. L’incidence des langues et de la communication sur l’accès, la qualité et la sécurité des soins acquiert une portée plus grande dans le contexte canadien où coexistent deux langues officielles. Nous partons de cette prémisse pour dresser ici le portrait de la santé mentale de la population francophone vivant en situation linguistique minoritaire à partir des données de l’Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC, 2012)[1]. Mots-clés : santé et maladies mentales, francophones en situation minoritaire, Canada, Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC)

La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)

The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

La santé en francophonie canadienne : vivre en situation minoritaire influence-t-il la santé ? - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène (Bulletin de l’association des médecins de langue française, 2009)
La littérature suggère l'hypothèse d'une santé différentielle des francophones en situation minoritaire au Canada. L'effet de minorité sur la santé perçue a été mesuré à l'aide des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) de 2001 et 2003. Une analyse de régression logistique multivariée séquentielle montre que les francophones minoritaires – hommes et femmes – sont plus enclins à déclarer une moins bonne santé que les anglophones majoritaires. Contrairement aux femmes, cette disparité chez les hommes demeure significative même lorsque nous ajustons pour certains grands déterminants de la santé. L'étude illustre que l'action des déterminants de santé peut être ainsi modulée par le rapport minoritaire/majoritaire. Les inégalités ainsi révélées appellent à une réflexion sur les politiques d'accès linguistique aux soins de santé.

Health profile of English-speaking minority communities in Quebec [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

Health profile of French-speaking minority communities in Canada [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

Profil santé des communautés anglophones minoritaires au Québec [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

Profil santé des communautés francophones minoritaires au Canada [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
Contexte : Les communautés francophones vivant en situation minoritaire évaluées à 1 million de personnes (4,4% de la population canadienne) sont dispersées un peu partout au pays. Les plus fortes concentrations sont en Ontario (509 265) et au Nouveau Brunswick (239 400), alors qu'ailleurs, on peut compter de 63 000 francophones (Alberta) à moins de 500 francophones (Nunavut). Ces communautés présentent un profil diversifié : elles sont en général moins jeunes, moins scolarisées, ont de plus faibles revenus. Elles sont davantage concentrés dans des régions où l'économie est plus instable rendant ainsi plus difficile le développement et l'accès aux ressources sociales. L'objectif de cette affiche est de présenter une sélection d'indicateurs décrivant certains aspects des déterminants de la santé de la population francophone en situation linguistique minoritaire. Méthode : Les indicateurs de santé sont extraits d'une analyse secondaire de l'ESCC combinant les cycles 2001, 2003 et 2005. L'analyse se fonde sur un échantillon d'adultes de 25 ans et plus de 244 382 : 12 583 francophones ; 256 966 anglophones. Le profil montre les situations et les déterminants les plus défavorables comparant la communauté minoritaire à la majorité anglophone dans l'ensemble du Canada excluant le Québec. Résultats : Sur l'ensemble des indicateurs sélectionnés (variables sociodémographiques, santé perçue, présence de maladie, difficulté à accomplir une tâche, services de santé, styles de vie, le sentiment d'appartenance), les communautés francophones présentent un profil de santé plus défavorable que la majorité anglophone et ce de façon plus marquée dans certaines zones géographiques. Conclusion : Les résultats permettent de soutenir que le rapport minoritaire/majoritaire semble traduire une inégalité sociale et d'accès aux ressources qui, traversée par les autres déterminants sociaux de la santé (statut socioéconomique, éducation et littératie, immigration) contribue de facto aux disparités de santé. Ils montrent l'importance d'approfondir et de mieux comprendre l'ensemble des déterminants de la santé ainsi que les interactions entre les contextes, les milieux de vie locaux, l'impact des politiques et la santé.

La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé, 2009)

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Capital social et minorités francophones au Canada - Bouchard, Louise; Gilbert, Anne (Francophonies d’Amérique, 2005)

Capital social, santé et minorités francophones - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Revue canadienne de santé publique / Canadian Journal of Public Health, 2006)

Social capital, health and Francophone minorities - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Canadian Journal of Public Health / Revue canadienne de santé publique, 2006)
The goal of this article is to outline the analytical perspectives of the concept of social capital regarding health and health management. Social capital, as defined in terms of social networks and resources, has a positive impact on a number of areas, notably the health, well-being, and social and economic development of communities. It is also a useful tool for implementing social policy, especially for marginal populations, the elderly, social assistance payments, etc. An action strategy based on the support and development of networks is the key to achieving the social development, health, and well-being of populations. The social ties promoted by these networks provide people with social, cognitive, and emotional support. This has a direct impact on their self-esteem and sense of personal achievement. They also facilitate access to social resources, including social advancement opportunities. In this paper, we examine the vitality, determinants of health, and health management of Canada’s minority Francophone communities.

Health profile of English-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Health profile of French-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Profil santé des communautés anglophones en situation minoritaire au Québec [infographie] - Bouchard, Louise; Sampasa-Kanyinga, hugues; Mukaneza, anne (2018)

Profil santé des communautés francophones en situation minoritaire au Canada [infographie] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

Langue minoritaire et services de santé mentale en l’an 2000 : droits et besoins des francophones de Toronto - Boudreau, Françoise (Reflets, 1999)

Profil épidémiologique des francophones de l’Ontario : les faits saillants revisités et comparés - Boudreau, Françoise; Farmer, Diane (Reflets, 1999)

Bilingual health care in Quebec: Public policy, vitality, and acculturation issues - Bourhis, Richard Y. (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Abstract The first part of this chapter offers the Interactive Acculturation Model (IAM), which provides an intergroup approach to minority/majority group relations in multilingual settings. The ethnolinguistic vitality framework is the first element of the IAM as it describes the relative strength and weaknesses of linguistic communities in contact. Four language policies regulating the status of linguistic communities constitute the key second element of the IAM. Third, the acculturation orientations of minority and majority group speakers are described as they interact to yield harmonious, problematic or conflictual intergroup relations. As an application of the IAM, the second part of the chapter analyzes bilingual health care policies for official language minorities in Canada and Quebec. A detailed analysis of bilingual health care institutions serving the English-speaking communities of Quebec closes with a case study of a recent Quebec Government health care law that threatened to undermine the institutional vitality of the Anglophone minority of Quebec. Key words: Interactive Acculturation Model (IAM), English-speaking communities of Quebec, health care policies.

The vitality of the English-speaking communities of Quebec: From community decline to revival - Bourhis, Richard Y. (Centre d’études ethniques des universités montréalaises, Université de Montréal, 2008)

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

Suicide mortality gap between Francophones and Anglophones of Quebec, Canada - Burrows, Stephanie; Auger, Nathalie; Tamambang, Lum; Barry, Amadou. D. (Social psychiatry and psychiatric epidemiology, 2013)
Purpose Few studies evaluate language-group differences in suicide mortality. This study assessed the suicide mortality gap between Francophones and Anglophones of Quebec, Canada according to age, sex, method, region and socioeconomic deprivation. Methods Suicide decedents were extracted from the Quebec death file for 1989–2007 (N = 24,465). Age- and sex-specific suicide mortality rates were calculated for four periods (1989–1993, 1994–1998, 1999–2003, 2004–2007) for Francophones and Anglophones aged ≥10 years. Age-standardized rates of suicide by method, region, and level of social and material deprivation were calculated for each sex. Rate ratios and rate differences were estimated. Results Suicide rates for Francophones were two to three times higher than rates for Anglophones, and differences were greatest for adults aged 25–64 years. Francophone males had more than two times the rate of suicide by hanging or firearms than Anglophone males. Francophone females had twice the rate of hanging, poisoning or firearm suicide as Anglophone females, although precision was low. Francophone-Anglophone suicide mortality gaps were higher in urban areas despite lower suicide rates, and varied little across levels of social and material deprivation. Conclusions There was a large suicide mortality gap between Francophones and Anglophones of Quebec; especially, among adults aged 25–64 years.

Instantané de recherche : portrait de la santé mentale des Canadiens francophones en situation minoritaire - CAMH-Evidence Exchange Network (2020)

Quel avenir pour les services sociaux et de santé des communautés anglophones du Québec ? - Carter, Jane (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)

Profil génétique et prévalence de la fibrose kystique dans les communautés acadiennes et francophones des Maritimes - Chappe, Frédéric; McGrath, Karla; Robinson, Walter; Chappe, Valérie (Francophone d'Amérique, 2009)
Nous évaluons ici la situation des Acadiens et des francophones des provinces maritimes (Nouvelle-Écosse, Nouveau-Brunswick, Île-du-Prince-Édouard) face à la fibrose kystique, la maladie génétique létale la plus répandue en Amérique du Nord. Nos résultats indiquent que plusieurs familles acadiennes et francophones sont touchées par cette maladie et qu’il existe un besoin de documentation et de services en français, spécifiques aux communautés acadiennes. Des disparités régionales ont été observées pour l’âge au diagnostic et le profil génétique, notamment dans les régions à majorité francophone. Cette analyse confirme le besoin d’études spécifiques sur la santé des Acadiens et des francophones des Maritimes.

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

Vivre et travailler en français à Iqaluit (Nunavut) : regards de professionnels de la santé sur le capital social de la communauté francophone - Charrier, Marie-Josée (Revue du Nouvel-Ontario, 2019)

Les communautés francophones en situation minoritaire : un portrait de famille - Charron, Mathieu (Francophonies d’Amérique, 2014)
Les francophones du Canada vivent dans des environnements linguistiques diversifiés et doivent donc composer avec des contraintes et des conditions spécifiques. Ces particularités impliquent une variété de situations et proscrivent l’application d’un projet unique de développement des communautés. L’article propose une classification des communautés francophones qui tient compte des nombreuses réalités vécues. S’appuyant sur les données du recensement, une typologie de sept catégories est proposée : communautés traditionnelles, diversifiées, assimilées, volatiles, globales, cosmopolites et anglophones. Les spécificités statistiques et les distributions géographiques de chacune des catégories y sont présentées.

Are there mental health differences between Francophone and non-Francophone populations in Manitoba? - Chartier, Mariette Jeanne; Finlayson, Gregory; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; Walld, Randy; De Rocquigny, Janelle (The Canadian Journal of Psychiatry, 2014)
Objective: Francophones may experience poorer health due to social status, cultural differences in lifestyle and attitudes, and language barriers to health care. Our study sought to compare mental health indicators between Francophones and non-Francophones living in the province of Manitoba. Methods: Two populations were used: one from administrative datasets housed at the Manitoba Centre for Health Policy and the other from representative survey samples. The administrative datasets contained data from physician billings, hospitalizations, prescription drug use, education, and social services use, and surveys included indicators on language variables and on self-rated health. Results: Outside urban areas, Francophones had lower rates of diagnosed substance use disorder (rate ratio [RR] = 0.80; 95% CI 0.68 to 0.95) and of suicide and suicide attempts (RR = 0.59; 95% CI 0.43 to 0.79), compared with non-Francophones, but no differences were found between the groups across the province in rates of diagnosed mood disorders, anxiety disorders, dementia, or any mental disorders after adjusting for age, sex, and geographic area. When surveyed, Francophones were less likely than non-Francophones to report that their mental health was excellent, very good, or good (66.9%, compared with 74.2%). Conclusions: The discrepancy in how Francophones view their mental health and their rates of diagnosed mental disorders may be related to health seeking behaviours in the Francophone population. Community and government agencies should try to improve the mental health of this population through mental health promotion and by addressing language and cultural barriers to health services.

How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report, Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

Rapport au ministre fédéral de la santé - Comité consultatif des communautés francophones en situation minoritaire (Santé Canada, 2001)

La recherche, un levier pour améliorer la santé. 1er forum national de recherche sur la santé des communautés francophones en situation minoritaire - Consortium national de formation en santé; Société Santé en français (Santé Canada, 2005)

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Portrait des minorités de langue officielle au Canada : les francophones de l'Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Francophones in Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Analytical Paper, 2010)

Les Canadiens partiellement français sont susceptibles à une augmentation des facteurs de risque cardiovasculaire : une étude de cohorte rétrospective basée sur la population - Daccache, J.; Savoury, M.; Yam, Y.; Chow, B. J. M. (Annales de Cardiologie et d'Angéiologie, 2020)
Introduction Grâce à diverses recherches menées dans le passé, il a été démontré que le Québec est la province avec les taux d’infarctus aigü du myocarde (IAM) et la prévalence des facteurs de risque cardiovasculaire les plus élevés au Canada. Cette étude proposée effectuera une analyse rétrospective sur les populations caucasiennes, afin d’analyser les facteurs de risque cardiovasculaire dans les populations partiellement francophones par rapport aux Canadiens-Français et non-Français. En outre, nous analyserons de près les deux sexes des populations susmentionnées. Méthode Cette étude de cohorte rétrospective, basée sur la population, a été réalisée en utilisant le registre de l’ACTC de l’Institut de cardiologie de l’Université d’Ottawa (ICUO). Les participants sont des patients de race blanche de tout âge, qui sont venus à l’ICUO pour une angiographie par tomodensitométrie, entre 2006 et 2018, et qui ont donné leur consentement éclairé. SPSS a été utilisé pour comparer les différentes populations (Canadiens-Français [CF], Canadiens partiellement Français [CPF], et Canadiens non-Français [CNF]) et les différents sexes. Résultats La population des CPF ressemble plus à celle des FC, ayant une incidence plus élevée de facteurs de risque cardiovasculaire tels que le tabagisme, la dyslipidémie et le diabète de type 2. Interprétation Nos résultats suggèrent que les CPF, comme les CF, pourraient bénéficier d’une éducation plus intensive et de techniques de modification du mode de vie.

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Défis associés à l’offre de services de santé et de services sociaux en français au Manitoba : perceptions des professionnels - de Moissac, Danielle; de Rocquigny, Janelle; Giasson, Florette; Tremblay, Cindy-Lynne; Aubin, Natalie; Charron, Marc; Allaire, Gratien (Reflets, 2012)
Les services de santé et les services sociaux en français ne sont accessibles qu’auprès d’un quart de la population francophone au Manitoba (de Moissac, 2011). Une pénurie de professionnels pouvant offrir des services en français est perçue comme un obstacle important pour les usagers qui recherchent ces services et pour les professionnels qui voudraient assurer un suivi en français pour leurs clients. Une hésitation à s’identifier comme francophone et un manque de connaissance des ressources disponibles en français contribuent-ils à cette perception de pénurie? Cet article traite des défis entourant l’offre de services de santé et de services sociaux en français au Manitoba et suggère des pistes de solutions. Mots-clés : disponibilité, accessibilité, minorité francophone, Manitoba, professionnels

Besoins et services en français en matière de sexopérinatalité chez les couples parentaux franco-ontariens - de Pierrepont, Catherine; Polomeno, Viola; Bouchard, Louise; Reissing, Elke (Minorités linguistiques et société, 2017)
Cet article dévoile un portrait des besoins et des services en français en matière de sexopérinatalité perçus par 67 couples parentaux francophones en situation linguistique minoritaire d’Ottawa et de l’Est de l’Ontario. Les couples ont des besoins d’informations et de soutien ; pour eux, il est important d’aborder la sexualité pendant la période périnatale. Toutefois, le sujet est peu discuté avec les professionnels de la santé, et très peu de services sexopérinataux en français sont offerts, même s’ils sont souhaités par ces couples. Les discussions sur la sexualité qui se déroulent majoritairement en anglais constituent un obstacle supplémentaire pour une majorité des couples. Mots-clés : sexualité périnatale, couples parentaux, périnatalité, francophones en situation linguistique minoritaire, services de santé en français

Utilisation des services gouvernementaux de langue française. Une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités linguistiques, 2009)

Utilisation des services gouvernementaux de langue française : une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français : sommaire - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités liguistiques, 2010)

Problématique générale : Enjeux de l’accessibilité et de l’offre active de sociaux et de santé au sein de la francophonie canadienne en situation minoritaire - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; Laforge, M.-J. (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Cette problématique générale vise tout d’abord à présenter un portrait global des communautés francophones en situation minoritaire (CFSM) au Canada. Nous présenterons aussi la problématique de l’accessibilité à des services sociaux et de santé en français en contexte linguistique minoritaire, l’importance de l’accès à des services dans la langue officielle de son choix et les principaux éléments qui justifient le fait d’offrir activement des services sociaux et de santé en français dans les CFSM. Nous établirons également les bases d’une définition de l’offre active et certains contours politiques et historiques qui façonnent les services sociaux et de santé en français en contexte francophone minoritaire. Cette problématique générale sera, par conséquent, une assise pour chacun des chapitres qui composeront cet ouvrage et en facilitera la compréhension.

Identification des communautés anglophones du Québec : approche populationnelle dans le cadre de l’évaluation des disparités de santé associées à l’infarctus du myocarde - Drouin, Catherine; Courteau, Josiane; Orzanco, Maria Gabriela; Leroux, Denis; Vanasse, Alain (Revue d’études des Cantons-de-l’Est, 2011)
Il existe peu de données probantes permettant d’évaluer les disparités en matière de santé entre les groupes linguistiques au Québec. Ce projet propose une méthode de classification des communautés du Québec en fonction de l’appartenance linguistique de la population ainsi que l’association, basée sur le lieu de résidence des patients, des données médico-administratives et de celles du recensement. Ensuite, des comparaisons entre les groupes linguistiques quant aux traitements et au suivi des cas d’infarctus du myocarde, réalisées à l’aide de tests du Khi carré, permettent d’identifier que la principale disparité se manifeste dans les taux de revascularisation.

La santé communautaire en Ontario français : défis et espoirs [numéro thématique] - Dubois, Madeleine; Kérisit, Michèle (Reflets, 1995)

Implantation d’un programme de formation à l’offre active de services en français auprès des futurs professionnels de la santé et des services sociaux dans une université canadienne - Dubouloz-Wilner, Claire-Jehanne; Benoît, Josée; Savard, Jacinthe (Éducation francophone en milieu minoritaire, 2019)

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario - Duong, Patrick; Batista, Ricardo; Lizotte, Mathieu; Sauvé-Schenk, Katrine; Bouchard, Louise (2024)

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (Colloque 103 – L’offre des services de santé dans les langues minoritaires, dans le cadre du 92e Congrès de l’Acfas, 2025)

La recherche au profit d’un meilleur accès aux services de santé en français [numéro thématique] - Dupuis-Blanchard, Suzanne; Vézina, Sylvain (Minorités linguistiques et société / LinguisticnMinorities and Society, 2015)

Les disparités d'accès aux soins de santé parmi la minorité de langue officielle au Québec - Falconer, James; Quesnel-Vallée, Amélie (Recherches sociographiques, 2014)
Cette étude examine l’effet de l’aptitude en français sur la santé et sur les besoins de soins de santé non satisfaits au Québec, en utilisant un modèle multiple de régression logistique. Nos résultats indiquent que les anglophones unilingues du Québec sont 26 % plus susceptibles que les anglophones bilingues à se déclarer en mauvaise santé. Théoriquement, ce mauvais état de santé devrait mener à une utilisation accrue des soins de santé. Cependant, malgré leur mauvais état de santé, les anglophones unilingues sont 52 % plus susceptibles de déclarer des besoins en soins de santé non satisfaits. Ces disparités dans l’état de santé ainsi que dans l’accès aux soins de santé s’expliquent par l’aptitude à s’exprimer en français. Par ailleurs, ces effets ne sont pas modifiés par l’inclusion de variables potentiellement confondantes telles que les caractéristiques sociodémographiques et socioéconomiques. Les résultats suggèrent que ce sont les politiques visant à réduire les obstacles à l’accès aux soins de santé des populations minoritaires qui pourraient améliorer l’accès aux soins, et, éventuellement, la santé des anglophones unilingues du Québec. Mots-clés : populations minoritaires de langue officielle, anglophones, Québec, utilisation des services de santé, inégalités de santé, accès aux soins de santé

Le statut socioéconomique des anglophones du Québec : ceux qui sont partis et ceux qui sont restés - Floch, William; Pocock, Joanne (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)

Autonomie, vitalité et identité des communautés en situation minoritaire : proposition d’un cadre conceptuel - Forgues, Éric (Revue internationale d’études canadiennes, 2010)
Quels facteurs contribuent à la vitalité linguistique d’une communauté en situation minoritaire et lui assurent les conditions propres à favoriser sa reproduction linguistique et culturelle? Nous nous proposons de présenter un modèle conceptuel susceptible de répondre à cette question. Selon ce modèle, trois facteurs sont au fondement de la reproduction linguistique d’une communauté en situation minoritaire : la gouvernance, l’identité et la vitalité, avec comme point pivot, la société civile et l’espace public. Cet article présente non seulement la fonction de ces facteurs au sein des communautés, mais les sous-fonctions qui découlent de leurs interrelations, tels que la lutte pour la reconnaissance, le droit, la complétude institutionnelle, l’engagement social et l’expression identitaire publique et privée. Ce modèle peut être utile pour saisir, d’un point de vue global, les composantes de la reproduction des communautés en situation minoritaire, pour déterminer celles qui la compromettent et, ainsi, envisager des pistes d’action.

Liminaire: Les enjeux reliés à la santé des communautés francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Landry, Rodrigue (Francophonies d’Amérique, 2009)

De l’émergence à la consolidation. L’état de santé des francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Nkolo, Christiane; Boudreau, Jonthan (Consortium national de formation en santé et Institut canadien de recherche sur les minorités linguistiques, 2009)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement de 2001 - Forgues, Éric; Landry, Rodrigue; Boudreau, Jonathan (Institut canadien de recherche sur les minorités linguistiques et Consortium national de formation en santé, 2009)

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Un aperçu de la santé et de ses déterminants au Nouveau-Brunswick d’après les données des Enquêtes sur la santé des collectivités canadiennes (ESCC) 2001-2003-2005 - Gaboury, Isabelle; Bouchard, Louise (Université d'Ottawa, 2008)

Les données administratives et d’enquêtes sur l’état de santé et l’accès aux services des communautés francophones en situation minoritaire : potentiel d’analyse et état de situation. Rapport - Gaboury, Isabelle; Guignard Noël, Josée; Forgues, Éric; Bouchard, Louise (Consortium national de formation en santé, 2009)

Un aperçu de la santé et de ses déterminants dans la région Champlain de l’Est de l’Ontario d’après les données des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) 2001-2003-2005-2007 - Gagnon-Arpin, Isabelle; Gaboury, Isabelle; Bouchard, Louise (Université d'Ottawa, Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada, Institut de recherche sur la santé des population, 2009)

Le surplus de poids chez les francophones et les anglophones - Gagnon-Arpin, Isabelle; Makvandi, Ewa; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs Des études récentes rapportent une prévalence d’embonpoint et d’obésité plus élevée chez les francophones en situation linguistique minoritaire en comparaison à la majorité anglophone du Canada. L’objectif de l’étude est de vérifier si l’appartenance au groupe linguistique minoritaire s’ajoute aux déterminants sociaux du surplus de poids. Méthode Les statistiques descriptives (n=128 986), provenant de cinq cycles de l’Enquête sur la santé dans les collectivités canadiennes, ont été croisées en fonction de la langue et du sexe des individus. Deux modèles de régression logistique multivariée, pour les hommes et pour les femmes, ont permis de tester l’association entre le surplus de poids et la langue en contrôlant pour les déterminants socioéconomiques et comportementaux. Résultats La prévalence du surplus de poids est plus élevée chez les francophones que chez les anglophones de l’Ontario, bien que cette différence ne soit plus significative lorsque le modèle est ajusté pour les caractéristiques socioéconomiques et comportementales. Néanmoins, les francophones sont plus âgés, moins éduqués et vivent davantage en milieu rural que leurs homologues anglophones, un contexte qui les rend plus vulnérables. Conclusion L’étude vient réaffirmer le rôle des déterminants sociaux et comportementaux dans la prévalence du surplus de poids. Bien que la langue n’influence pas directement le surplus de poids, compte tenu de la réalité socioéconomique de la minorité francophone, représentée en plus grande proportion dans les strates de la population plus vulnérable au surplus de poids, l’appartenance à un groupe minoritaire devrait interpeller les planificateurs de la santé.

Portraits socio-sanitaires des communautés francophones de l'Ontario | Demographic and health profiles of Ontario's Francophone communities - Gagnon-Arpin, Isabelle; Sedigh, Golnaz; Bouchard, Louise (Alliance des réseaux ontariens de santé en français, 2011)

Les services de santé en français pour les communautés francophones et acadiennes en situation minoritaire du Canada : bonification du schéma du CCCFSM (2001) - Giguère, Louis (Nouvelles perspectives en sciences sociales, 2013)
Nous bonifions le schéma du CCCFSM (2001) sur le développement des services de santé en français pour les communautés francophones et acadiennes en situation minoritaire (CFASM) du Canada à l’aide de données probantes recueillies lors du recensement national de 2006. Notre approche consiste à choisir, à partir d’une procédure statistique, une mesure de masse critique de francophones qui met en évidence un schème cohérent d’offre et de demande de services de santé sur une base géographique juridictionnelle. L’offre et la demande sont plus grandes là où la vitalité linguistique des CFASM est plus grande. Dans l’ensemble, l’offre tombe en deçà de la demande; ceci suggère une demande latente de services en français et est consistant avec les études d’offre active des services en français dans les CFASM. Nos résultats sont aussi consistants avec les trois phases évolutives de sensibilisation, de structuration et de consolidation proposées par le CCCFSM (2001). Nous discutons des limitations méthodologiques et en tirons des leçons pour les réseaux de santé francophones des CFASM. Mots-clés : CFASM, CLOSM, communauté francophone, minoritaire, vitalité linguistique, langues officielles, réseaux de santé, services en français, offre et demande

Validation d’un schème national sur le développement des services de santé pour les communautés francophones et acadiennes en situation minoritaire au Canada : arrimage à des assises théoriques et modélisation - Giguère, Louis (Nouvelles perspectives en sciences sociales, 2014)
Nous avons présenté (Giguère, 2013), pour les communautés francophones hors Québec (CFASM), un schème juridictionnel national qui illustre l’offre et la demande de services de santé en français en fonction d’une masse critique de francophones qui reflète la vitalité linguistique de ces communautés. Nous corroborons ce schème à l’aide de procédures statistiques dont l’une identifie une forte association entre le rapport offre/demande (un ratio) et des facteurs qui reflètent la cohérence linguistique et culturelle des deux communautés de langue officielle. Ce résultat est cohérent avec le cadre de vitalité linguistique déjà proposé (Giguère, 2013), et il fait écho au travail de terrain de Forgues, Bahi et Michaud (2011) et aux modèles psycho-langagiers et d’autonomie culturelle de Deveau, Landry et Allard (2009), de Landry, Allard et Deveau (2007, 2008) et de Landry (2012). Nous modélisons le développement des services de santé en français pour les CFASM dans un cadre national structurant qui est cohérent avec ces assises empiriques et théoriques. Cette modélisation suggère deux approches stratégiques distinctes mais complémentaires pour favoriser le développement des services de santé en français. Mots-clés : CFASM, communauté francophone, minoritaire, développement communautaire, vitalité langagière, réseautage, schéma CCCFSM, assises théoriques, modélisation en diagramme de phase

L'environnement et la vitalité communautaire des minorités francophones : vers un modèle conceptuel - Gilbert, A.; Langlois, A.; Landry, R.; Aunger, A. E. (Territoires francophones : études géographiques sur la vitalité des communautés francophones du Canada, 2010)

Les discours sur la santé des organismes franco-ontariens : du rapport Dubois à la cause Montfort - Gilbert, Anne; Kérisit, Michèlle; Dallaire, Christine; Coderre, Cécile; Harvey, Jean (Reflets, 2005)

L’environnement et la vitalité communautaire des minorités francophones : vers un modèle conceptuel - Gilbert, Anne; Langlois, André; Landry, Rodrigue; Aunger, Edmund (Francophonies d'Amérique, 2005)

Comorbidités entre maladies chroniques et problèmes de santé mentale fréquents : différences entre francophones et anglophones - Grenier, Jean; Gosselin, Dominique; Greenman, Paul. Samuel; Chomienne, Marie-Hélène; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Psy-Cause, 2016)

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement. Mise à jour : recensement de 2011 - Guignard-Noël, Josée; Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques, 2014)

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

La littérat'ie en santé et les communautés francophones, minoritaires et ethnoculturelles - Kaszap, M.; Zanchetta, M. S. (Lire le monde : les littératies multiples et l'éducation dans les communautés francophones, 2009)

Do you speak English? Traitement sociopolitique de l’accessibilité aux services en santé mentale pour les anglophones du Québec - Kirouac, Laurie; Perreault, Isabelle (Minorités linguistiques et société, 2018)
À la fin des années 1970, le Québec se dote de la Charte de la langue française (Loi 101), qui modifie l’encadrement de la question de la langue de prestation des services de santé et de services sociaux. Parallèlement, de nombreux rapports, comités d’étude et politiques modifient en profondeur les pratiques institutionnelles et communautaires à l’endroit des personnes aux prises avec des problèmes de santé mentale. Depuis ce contexte de grandes transformations, où certaines réponses politiques ont été apportées aux préoccupations linguistiques, qu’en est-il de l’accès aux soins de santé mentale pour les anglophones du Québec ? Nous proposons de retracer dans ses grandes lignes l’évolution du traitement sociopolitique qui a été fait de la question de l’accessibilité des services en santé mentale pour les personnes anglophones en accordant une attention particulière à la situation montréalaise. Mots-clés : Québec, anglophones, santé mentale, minorité linguistique, services de santé

Modèle de mobilisation communautaire pour l’amélioration de la santé et de la vitalité des communautés d’expression anglaise au Québec - Kueber, Russell; Richardson, Mary (Réseau communautaire de santé et des services sociaux et Institut national de santé publique du Québec, 2019)

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistics Canada, 2009)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

Autodétermination du comportement langagier en milieu minoritaire : un modèle conceptuel - Lagacé, Josée; Lefebvre, Pascal (Francophonies d’Amérique, 2005)

Autonomie culturelle, cultures sociétales et vitalité des communautés de langue officielle en situation minoritaire au Canada - Landry, Rodrigue (Minorités linguistiques et société, 2012)
Partant d’un modèle macroscopique des facteurs associés à la vitalité d’une minorité linguistique en situation intergroupe, cet article présente cinq principes expliquant comment les structures sociales s’imposent sur les vécus langagiers des membres de la minorité. Ce même modèle montre comment tant les individus que la collectivité peuvent exercer leur autonomie langagière pour contrer ce déterminisme social. Le modèle de l’autonomie culturelle est explicité et appliqué aux communautés de langue officielle en situation minoritaire (CLOSM) dans le but de faire valoir leur besoin d’autonomie institutionnelle pour assurer leur vitalité au Canada. La reconnaissance du droit à l’autonomie culturelle pourrait être un mode de légitimation des droits propres à ces communautés. Les CLOSM sont décrites comme des prolongements des deux cultures sociétales qui constituent le fondement de la dualité linguistique canadienne. Mots-clés : autonomie culturelle, culture sociétale, vitalité linguistique, droits linguistiques, minorités linguistiques

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Peut-on parler d'une déshospitalisation des services ? Les soins en santé mentale de la minorité de langue officielle dans le Nord-Est ontarien - LeBel, Marie (La fin de l'asile ? Histoire de la déshospitalisation psychiatrique dans l'espace francophone au xxe siècle, 2018)

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.

Impact de la crise de la COVID-19 sur les familles francophones dans les Prairies canadiennes - Leis, Anne; De Moissac, Danielle; Proulx-Cullen, Elyse; Gnidehou, Sedami; Marchak, Kristan A.; Keough, Catelyn; Chaput, Mélanie; Turgeon, Marianne (Minorités linguistiques et société, 2025)
Contexte et but. Dans le contexte linguistique minoritaire où l’accès à des services en français est un défi, l’étude voulait documenter dans quelle mesure la crise de la pandémie avait eu un impact sur les familles francophones au Manitoba, Saskatchewan et Alberta. Méthodes. À partir des informations recueillies lors de 6 World Café du Monde, un sondage a été créé et distribué en ligne aux membres d’organismes francophones dans ces provinces. Des analyses descriptives et de régression ont été menées. Résultats. Des 319 familles, la grande majorité a reconnu l’impact négatif et anxiogène de la pandémie. Plusieurs facteurs de risque ont été identifiés : une compréhension moyenne ou faible de l’anglais, la déconnexion avec la communauté francophone locale, la difficulté de vivre en français en famille et de suivre la scolarité de ses enfants à la maison. Conclusion. La pandémie a été un défi pour les familles francophones des Prairies. Des ressources accrues en français et des politiques de soutien sont recommandées. , Background and aim. Within the linguistic minority context where access to services in French is a challenge, the study aimed to document to what extent the pandemic had an impact on Francophone families in Manitoba, Saskatchewan and Alberta. Methods. Based on the qualitative analysis of data collected in 6 World Cafés, an on-line survey was distributed to members of Francophone organizations in these provinces. Descriptive and regression analyses were conducted. Results. Of 319 families, the majority recognized the negative and anxiety provoking aspects of the pandemic. Several risk factors were identified: an average or below average mastery of English, isolation from the local Francophone community, difficulty with living in French with their family and supporting children’s education at home. Conclusion. The pandemic was a challenge for Francophone families in the Prairies. Additional resources in French and supportive policies are recommended.

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)

Health care professionals and official-language minorities in Canada, 2001 and 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistics Canada, 2017)

Identité, culture et représentations de la santé et des maladies - Lévesque, Annabel (Cahiers franco-canadiens de l’Ouest, 2015)
La santé et les maladies représentent des concepts subjectifs qui varient en fonction de nombreux facteurs, notamment la culture d’appartenance. Étant donné le contexte multiculturel canadien, il importe de considérer le contact interculturel lorsqu’on s’interroge au sujet des représentations de la santé et des maladies chez les groupes minoritaires puisque ces derniers sont soumis à l’influence d’autres cultures, dont la culture du groupe dominant. Ainsi, le degré d’identification à la culture d’origine et à la culture dominante détermine les représentations auxquelles souscrivent les individus issus d’un groupe minoritaire. Chez ceux qui s’identifient à leur culture d’origine, on note un lien entre leur état de santé et la vitalité culturelle et linguistique de leur communauté. Les efforts visant à promouvoir la santé et le bien-être de ces individus devraient donc être axés sur le maintien de leur héritage culturel et linguistique. Les professionnels de la santé, pour leur part, devraient engager le dialogue avec leurs patients au sujet de leurs représentations culturelles de la santé et des maladies, et ce, dans un climat empreint de respect. Cette pratique pourrait contribuer à la satisfaction des patients avec les soins reçus et, par le fait même, à l’adoption de comportements sains.

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Participation citoyenne, francophonie minoritaire et gouvernance des services de santé : les conceptions des acteurs - Lévesque, Maurice; Burlone, Nathalie; Boyer, Émilie (Université d'Ottawa, 2010)

La situation socioéconomique des anglophones du Québec - Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2012)

The socioeconomics status of Anglophones in Québec - Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2012)

Lifestyle habits and health indicators of Québec Anglophones - Lussier, Marie-Hélène; Trempe, Normand (Institut national de santé publique du Québec, 2013)

Quelques habitudes de vie et indicateurs de santé des anglophones du Québec - Lussier, Marie-Hélène; Trempe, Normand (Institut national de santé publique du Québec, 2013)

À l’intersection des définitions de langues : portrait des communautés linguistiques au Québec et dans les réseaux territoriaux de services en 2016. La langue, déterminant de l'état de santé et de la qualité des services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

At the intersection of language definitions: A portrait of linguistic communities in Québec and its territorial service networks in 2016. Language as determinant of health and quality of services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Les soins de santé en français à l'extérieur du Québec - Marmen, L.ouise; Delisle, Sylvain (2003)

Santé mentale - Michel, Isabelle; Lévesque, Johanne (Programme de recherche, d'éducation et de développement en santé publique, Institut franco-ontarien et Université Laurentienne, 2005)

Expérience de conciliation travail-famille de parents francophones de la région d’Ottawa : étude pilote - Moreau, Denise; Polomeno, Viola; Ranger, Marie-Christine (Reflets, 2018)
Plusieurs études soutiennent que l’expérience de la conciliation travail-famille (CTF) a un impact majeur sur la santé et la qualité de vie des familles (Winter, et collab., 2006). Les objectifs de cette étude pilote étaient les suivants : 1) documenter l’expérience de la CTF chez un groupe de parents francophones de la région d’Ottawa, 2) élaborer, pré-tester et administrer le questionnaire sur l’expérience de conciliation travail-famille (ECTF), et 3) exécuter les premières étapes de validation de cet instrument. Cet article présente les données recueillies auprès de 46 participantes et participants concernant leurs expériences et leurs stratégies de CTF ainsi que leurs suggestions pour favoriser la CTF. Mots-clés : conciliation travail-famille, parents, francophones, étude pilote, Ottawa

The linguistic continuity of Ontario's minority Francophone population: Examining the relationship between culture and linguistic practices - Nault, Jean-François (Canadian Review of Sociology, 2019)
Despite decades of policy aimed at the maintenance of Francophone communities in Ontario, the proportion of individuals with French as a mother tongue or who speak French most often at home has steadily declined. Research on language retention has highlighted the importance of sociodemographic and structural factors in understanding minority language practices. However, given the relationship between culture and action, this paper examines how cultural factors contribute to Franco-Ontarians’ linguistic practices. Results indicate that beyond couple composition and the concentration of minority-language speakers, cultural factors including identity, cultural consumption, and values play an instrumental role in Franco-Ontarians’ linguistic continuity. The importance of considering linguistic continuity as part of a “package” of cultural practices is discussed.

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)

Besoins et lacunes en matière de services de santé en français dans l’Est Ontario - Ouellette, Rachel; Mailhot, Renald (Réseau des services de santé en français de l’Est de l’Ontario, 1999)

Adaptation linguistique des soins et des services de santé : enjeux et stratégies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Language adaptation in health care and health services: Issues and strategies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Hôpital Montfort : reflets de la francophonie en évolution - Perron Roach, Daniel (Reflets, 2015)

Étude de besoins sur les services de santé mentale en français. Rapport final - PGF Consultants (Société Santé en français et Santé Canada, 2019)

Deuxième rapport sur la santé des francophones de l’Ontario - Picard, Louise; Allaire, Gratien (Programme de recherche, d'éducation et de développement en santé publique, Institut franco-ontarien et Université Laurentienne, 2005)

La santé des francophones à l’aube de l’an 2000 - Picard, Louise; Carrière, Richard; Hébert, Denise (Reflets, 1999)
Neuf articles contenus dans ce numéro spécial sur la danté des francophone à l'aube de l'an 2000 analysent l’état de la santé de la population francophone et décrivent des modèles, des pratiques et des programmes de santé et de promotion de la santé, dont certains innovent au niveau de la formation des professionnels de la santé. Ce numéro de Reflets n’est pas exhaustif, loin s’en faut! Cependant, il se veut un outil de réflexion et un intervenantes dans les domaines qui touchent la santé.

Le profil démographique et les déterminants de la santé des francophones en Ontario - Picard, Louise; Charland, Janine (Reflets, 1999)
Afin de mieux cerner l’état de santé des francophones à l’aube de l’an 2000, il est important de comprendre leur contexte social. En effet, plusieurs variables, tels l’alphabétisme, l’éducation ou le revenu affectent directement et indirectement la santé des personnes. Ainsi, dans un effort de compréhension du contexte social dans lequel évoluent les Francophones, cet article cherchera à résumer les traits principaux qui caractérisent cette société, à partir des analyses démographiques menées par l’Office des affaires francophones et le Programme de recherche, éducation et développement du Ministère de santé de l’Ontario. Ces analyses s’appuient sur les données les plus récentes de Statistique Canada, extraites du Recensement canadien de 1996.

L’état de santé de la population francophone de l’Ontario - Picard, Louise; Hébert, Denise (Reflets, 1999)
À l’aube de l’an 2000, afin de mieux planifier les services et les programmes en matière de santé pour la population francophone de l’Ontario, il faut avoir accès à des renseignements fiables et récents sur son état de santé. Jusqu’à maintenant, certaines études ont abordé des aspects particuliers de la santé des francophones de l’Ontario, comme celui des femmes francophones, des personnes aînées, de certaines régions ou comtés de la province. De plus, elles ont traité de problématiques spécifiques telles le tabagisme ou l’usage de l’alcool et des drogues. Toutefois, ces études ne permettent pas d’avoir un portrait global de la santé de l’ensemble de la population francophone. Par conséquent, le Programme de recherche, d’éducation et de développement en santé publique (REDSP) du ministère de la Santé de l’Ontario a entrepris de faire une étude afin d’établir ce portrait, dont les résultats sont contenus dans le Rapport sur la santé de francophones de l’Ontario (REDSP 1999). Dans cet article, on présentera: - quelques précisions méthodologiques. - les principales constatations contenues dans le Rapport sur la santé des francophones de l’Ontario. - une comparaison de l’état de santé des francophones à celui de l’ensemble de la population de la province. - la perception qu’ont les francophones de l’Ontario de leur état de santé général, les principaux problèmes chroniques de santé qui les affectent ainsi que leur état de santé mentale. -leurs comportements en matière de santé. Finalement, comme le rapport a été principalement rédigé à l’intention des planificateurs, des décideurs et des intervenants en santé publique, on accordera une attention particulière à l’identification des besoins actuels des francophones de l’Ontario. Ainsi, après avoir présenté un portrait global de leur état de santé, on suggèrera quelques pistes afin de faciliter la prestation de services de qualité adaptés aux réalités culturelles, linguistiques, voire géographiques, de la population franco-ontarienne.

Rapport sur la santé des francophones de l'Ontario, Sudbury - Picard, Louise; Sanderson, Ruth; Michel, Isabelle; Palangio, Alissa; Fraser, C.; Hébert, D.; Charland, J. (Programme de recherche, d’éducation et de développement en santé publique, Institut franco-ontarien et Université Laurentienne, 2000)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Demographic Profile of the English-Speaking Communities - Pocock, Joanne (2018)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

Substance Use, Addiction and Support Services: Increased Risk and Service Inequity for Official Language Minority Communities in Canada - Prada, Kevin; de Moissac, Danielle (The Canadian Journal of Addiction, 2024)
Abstract Objectives: The increase in substance use and addictions within the Canadian population, illustrated by the current opioid crisis and exacerbated by the COVID-19 pandemic, urges the investigation of populations who may be particularly vulnerable to developing problematic substance use. Official language minority communities in Canada, both understudied and underserved, may be one such population. Methods: Through its tripartite design using scoping literature review, interview, and environmental scan methodologies, this study offers a snapshot of the current reality surrounding substance use, addictions, and related treatment services available to this linguistic minority population. Results: Results reveal significant gaps in knowledge and service provision for this population. Service provision and knowledge on this issue constitute a nationwide patchwork, leaving official language minority communities underserved. While enough is known to assert that their needs are different than those of their majority peers, much remains to be investigated, and efforts to ameliorate their social determinants of health, including cultural and linguistic competence on behalf of service providers, are urgently needed. Conclusions: Recommendations include networking, collaboration, financial support and active offer of services in both official languages to improve mental health and addictions services through a continuum of care. Systems navigators may facilitate promotion and referral to such services for official language minorities. Résumé Objectifs: La prévalence croissante de la consommation des substances et des dépendances au Canada, tel qu’illustrée par la crise actuelle des opioïdes et exacerbée par la pandémie de la COVID-19, exhorte à l’investigation de populations qui pourraient être particulièrement vulnérables à la consommation problématique de substances. Au Canada, les communautés de langue officielle en situation de minorité (CLOSM), une population à la fois peu étudiée et peu desservie, pourrait bien représenter une telle population. Méthodes: Au moyen de sa stratégie tripartite, employant les méthodologies d’étude de la portée, d’entrevues, et de scan environnemental, cette étude brosse un premier portrait de la réalité actuelle quant à la consommation de substances, aux dépendances et aux services qui y sont voués, parmi les CLOSM au Canada. Résultats: Les résultats révèlent une lacune importante aux niveaux des connaissances et des services desservant les CLOSM dans la majorité des provinces et territoires. Bien que l’état des lieux soit parcellaire en raison du manque d’études scientifiques sur la question, le portrait actuel suffit pour constater que les besoins des CLOSM différent de ceux de leurs pairs de langue majoritaire. Une amélioration des déterminants sociaux de la santé, tel la compétence culturelle et linguistique de la part des pourvoyeurs des services, représente un besoin pressant. Conclusions: Les recommandations, qui comprennent le réseautage, la collaboration, l’appui financier et l’offre active des services dans les deux langues officielles, visent à améliorer les services voués à la santé mentale et aux dépendances auprès des CLOSM au sein d’un continuum de soins. Les navigateurs.rices de systèmes pourraient faciliter l’aiguillage de membres des CLOSM vers ces services.

Ciel éclairci ! Vers un meilleur accès aux services de santé mentale et de lutte contre les dépendances en français en Ontario - Programme de soutien au système provincial (Centre de toxicomanie et de santé mentale, 2018)

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Améliorer l’état de santé des francophones de Terre Neuve-et-Labrador - Réseau Santé en français de Terre-Neuve-et-Labrador (2021)

Santé mentale en français. Comprendre les enjeux et l’urgence de collaborer aux TNO - Réseau TNO Santé (Comprendre les enjeux et l’urgence de collaborer aux TNO, 2018)

Enquête sommaire sur la santé des francophones de Colombie-Britannique - RésoSanté Colombie-Britannique (2016)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

La francophonie boréale : la vitalité des communautés francophones dans les territoires. - Robineau, Anne; Traisnel, Christophe; Forgues, Éric; Guignard Noël, Josée; Landry, Rodrigue; Ministère du Patrimoine canadien; Commissariat aux langues officielles (Institut canadien de recherche sur les minorités linguistiques, 2010)

La recherche en santé et en services sociaux auprès des populations francophones en situation minoritaire au Canada. Revue de littérature et analyse des thèmes de recherche (2014-2016) - Sauvageau, Marie-Michèle (Association des collèges et universités de la francophonie canadienne, 2018)

Les professionnels de la santé et des services sociaux intervenant auprès des francophones minoritaires : l’enjeu du capital social - Savard, Sébastien; Arcand, Isabelle; Drolet, Marie; Benoît, Josée; Savard, Jacinthe; Lagacé, Josée (Francophonies d’Amérique, 2013)
Cet article présente les résultats d’une recherche qualitative sur la collaboration et le partenariat entre les professionnels des services sociaux et de la santé qui interviennent auprès de francophones vivant en situation minoritaire en Ontario. L’étude met en lumière, à partir de l’information recueillie auprès de 43 professionnels rencontrés dans huit groupes de discussion, le contexte qui caractérise leur pratique, les défis qu’ils rencontrent dans leur tentative de créer des liens de collaboration avec d’autres professionnels qui oeuvrent auprès des communautés francophones minoritaires ainsi que les facteurs qui facilitent l’établissement de partenariats entre les différents intervenants qui répondent aux besoins de cette population. Les résultats font ressortir que le sentiment d’appartenance, la confiance et l’engagement des professionnels envers la communauté francophone, de même que les valeurs de réciprocité et de solidarité qui les habitent sont des éléments qui favorisent le développement du capital social de la communauté des intervenants. Cependant, le manque de mécanismes permettant la consolidation et la pérennisation des relations de collaboration constitue un facteur qui limite la capacité de bonifier le capital social des professionnels de la santé et des services sociaux francophones et bilingues.

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Santé des francophones et utilisation des services de santé dans les Réseaux locaux d’intégration des services de santé d’Érié St.Clair et du Sud-Ouest - Smith, Michaela (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2013)

Pour une réforme de la santé respectueuse des deux communautés linguistiques officielles. Mémoire présenté à l’honorable Dorothy Shephard, ministre de la Santé, dans le cadre de la consultation publique sur l’avenir des soins de santé dans la province du Nouveau-Brunswick - Société de l'Acadie du Nouveau-Brunswick (2021)

Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients - Société Santé en français (2019)

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)

Préparer le terrain : soins et services de santé primaires en français au Nouveau-Brunswick - Société Santé et Mieux-être en français du Nouveau Brunswick (Préparer le terrain : soins et services de santé primaires en français au Nouveau-Brunswick)

Mémoire sur l’accès aux soins de santé primaires au Nouveau-Brunswick - Société Santé et Mieux-être en français du Nouveau-Brunswick; Mouvement Acadien des Communautés en Santé du Nouveau-Brunswick Inc (2011)

Quand la langue fait une différence. Ce que des « bénéficiaires » pensent du système de santé mentale - St-Amand, Nérée; Vuong, Dung (Sociologie et sociétés, 2002)
Résumé En partant d'une recherche effectuée en 1993 auprès d'une soixantaine d'ex-psychiatrisés néo-brunswickois qui fréquentent maintenant des réseaux d'entraide de cette province, cet article met en évidence certains des enjeux auxquels sont confrontées les personnes " trans-institutionnalisées ". Il en ressort plusieurs différences au niveau de l'utilisation des services et du degré de satisfaction, selon l'appartenance sexuelle et la langue en particulier. De plus, cette recherche démontre que le réseau sur lequel s'appuient les ex-psychiatrisés francophones interrogés est davantage social (familles, groupe d'entraide), alors que pour la population anglophone, l'appareil institutionnel (psychiatres, institutions et cliniques) joue un rôle déterminant. Ceci soulève plusieurs questions, tant au niveau des politiques sociales que des pratiques d'intervention, en contexte minoritaire en particulier. Abstract On the basis of research carried out in 1993 on sixty or so ex-psychiatric patients who now frequent mutual aid networks in New Brunswick, this paper points out some of the issues with which these 'trans-institutionalized' persons are confronted. Differences at the level of service use and degree of satisfaction stand out, particularly in relation to gender and language. Moreover, this research shows that the network on which Francophone ex-psychiatric patients depend is more social in nature (families, mutual aid groups), whereas for the Anglophone population the institutional apparatus (psychiatrists, institutions and clinics) play a determining role. This brings up several questions, in regards to social policies as well of intervention practices, particularly in the minority context. Resumen Partiendo de una investigación efectuada en 1993 sobre unos sesenta ex-pacientes psiquiátricos de Nueva Brunswick que frecuentan actualmente la red de ayuda mutua de esta provincia, este articulo pone en evidencia algunas de las disyuntivas a las cuales se ven confrontadas las personas " trans-institucionalizadas ". Resaltan varias diferencias a nivel de la utilización de servicios y del grado de satisfacción, particularmente según la pertenencia sexual y el idioma. Además, esta investigación demuestra que la red sobre la cual se apoyan los ex-pacientes psiquiátricos francófonos interrogados, es mucho más social ( familia, grupo de ayuda mutua) mientras que para la población anglófona, el aparato institucional (psiquiatras, instituciones y clínicas) juega un rol determinante. Esto sugiere varias preguntas, tanto a nivel de las políticas sociales como de las prácticas de intervención, particularmente en un contexto minoritario.

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.

Mortality in Francophone minority in Canada - A 16-year follow-up study. Mortality by socioeconomic status among canadian Francophones and Anglophones living outside Québec - Sucha, E.; SIlva, E.; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec - Sucha, Ewa; Silva, Erika; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

La satisfaction des patients francophones de l’Est de l’Ontario traités en réadaptation à domicile - Tardif, Charles; Dallaire, Christine (Francophonies d’Amérique, 2010)
L’accès à des services de santé en français est aujourd’hui une des revendications importantes des porte-drapeaux francophones non seulement pour assurer la santé individuelle des francophones mais aussi pour favoriser la vitalité des communautés. Cependant, certains des francophones qui font appel aux soins ou à l’appui des professionnels de la santé demandent des services en français, alors que d’autres sont satisfaits de recevoir des services en anglais. Cette étude s’inspire de l’analyse des discours développée par Michel Foucault pour examiner les discours que reproduisent les francophones qui reçoivent des soins de réadaptation à domicile, en français et/ou en anglais. Des entrevues semi-dirigées ont été effectuées avec 12 patients francophones dans l’Est de l’Ontario. Les participants de l’étude sont de façon générale satisfaits des soins reçus, mais la langue des services ne répond pas nécessairement à leurs attentes. Ce sont évidemment ceux qui ne peuvent s’exprimer en anglais, d’une part, et ceux qui s’affichent fièrement comme francophones, d’autre part, qui préfèrent recevoir des soins en français. Toutefois, ce ne sont pas que les caractéristiques linguistiques et identitaires des patients qui influencent les critères qu’ils jugent prioritaires pour évaluer les soins reçus. En effet, leur façon de concevoir leur rapport vis-à-vis le professionnel de la santé joue aussi sur l’importance qu’ils accordent à la langue des soins.

Comparing mental health of Francophone populations in Canada, France, and Belgium: 12-month prevalence rates of common mental disorders (part 1) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Bonnewyn, Anke; Lépine, Jean-Pierre; Gasquet, Isabelle; Mosier, Karen; Lesage, Alain; Puchala, Chassidy; Lepnurm, Marje; et al. (The Canadian Journal of Psychiatry, 2010)
Objective: To compare the 12-month prevalence of common mental disorders among francophones in Canada, France, and Belgium. This is the first article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: This is a secondary analysis of data from the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2) in 2002 and the European Study of Epidemiology of Mental Disorders-Mental Health Disability (ESEMeD) from 2001 to 2003, where comparable questionnaires were administered to representative samples of adults in Canada, France, and Belgium. In Canada, francophone respondents living in Quebec (n = 7571) and outside Quebec (n = 500) completed the French version of the CCHS 1.2 questionnaire. Francophone respondents in Belgium (n = 389) and in France (n = 1436) completed the French version of the ESEMeD population survey questionnaire. Major depressive episodes (MDEs), specific anxiety disorders (ADs), and alcohol abuse and (or) dependence disorders' rates were assessed. Results: The overall prevalence rate for the presence of any MDE, AD, or alcohol abuse and (or) dependence was similar in all francophone populations studied in Canada and Europe and averaged 8.5%. Conclusions: Mental disorders were equally distributed in all francophone populations studied. Cross-national comparisons continue to be instrumental in providing information useful for the creation of appropriate policies and programs for specific subsets of populations.

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

Access to psychiatrists by French-speaking patients in Ontario hospitals: 2005 to 2013 - Tempier, TempierRaymond; Bouattane, El Mostafa; Hirdes, John P. (Healthcare Management Forum, 2015)
There has been a limited amount of research suggesting that cultural and linguistic variables may affect access to health services, but no study has examined the access of French-speaking Canadians to psychiatrists. The present study used data from the Ontario Mental Health Reporting System to examine patterns of daily contact with psychiatrists in the first 3 days of admission to mental health facilities in Ontario. The results showed that after controlling for a broad range of covariates, French-speaking Ontarians were about one-third as likely to have daily contact with psychiatrists in that time period compared to English-speaking patients. These results were not explained by regional differences. Instead, they point to the possibility that language poses an important barrier to specific and highly specialized mental health services in this province.

Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. - Thifault, Marie-Claude (Le moment Monfort dans la francophonie canadienne, 2024)

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Pour des services de santé culturellement et linguistiquement adaptés - Tremblay, Suzanne (Société Santé en français et Société Santé et Mieux-être en français du Nouveau-Brunswick, 2011)
Ce document fait rapport des études : Les normes de compétences culturelles et linguistiques en santé : étude exploratoire sur les normes américaines et Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien.

Avoidable mortality of the two main linguistic communities in Québec. Language as a determinant of health status and service quality - Trempe, Normand; Diogo Barry, Amadou D.; Lussier, Marie-Hélène.; Lo, Ernest (Institut national de santé publique du Québec, 2013)

La mortalité évitable des deux principales communautés linguistiques du Québec. La langue, déterminant de l'état de santé et la qualité des services - Trempe, Normand; Diogo Barry, Amadou; Lussier, Marie-Hélène; Lo, Ernest (Institut national de santé publique du Québec, 2013)

Knowledge and use of the English language by healthcare and social services professionals in Québec - Trempe, Normand; Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2011)

La connaissance et l'utilisation de la langue anglaise par les professionnels de la santé et des services sociaux au Québec - Trempe, Normand; Lussier, marie-Hélène (Institut national de santé publique du Québec, 2011)

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.

Bilan de santé : une analyse descriptive de l’état de la recherche sur la santé et les communautés francophones en situation minoritaire - Vézina, Sylvain (Minorités linguistiques et société, 2015)
Ce texte présente un bilan des activités de recherche soutenues par le Consortium national de formation en santé (CNFS), selon l’orientation des connaissances produites et des pistes d’action qui en résultent. Nous y abordons la question de la participation du milieu à la planification de la recherche, sa réalisation et la mise en pratique des résultats. L’étude a été réalisée selon deux méthodes : une analyse du contenu des documents produits et une série d’entrevues avec des chercheurs et des représentants du milieu. L’objectif consiste à fournir quelques indications sur les atouts et les défis du rapprochement entre chercheurs et communautés dans la perspective de la recherche participative. Mots-clés : production en recherche, santé des minorités, minorité francophone du Canada, mise en pratique des connaissances, recherche participative, rapprochement chercheurs-communautés

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.